Evidence-based chronic heart failure management programs: reality or myth?. Issue 6 (2nd December 2009) - Driscoll, A; Worrall-Carter, L; Hare, D L; Davidson, P M; Riegel, B; Tonkin, A; Stewart, S
Abstract : Background: Chronic heart failure management programmes (CHF-MPs) have become part of standard care for patients with chronic heart failure (CHF). Objective: To investigate whether programmes had applied evidence-based expert clinical guidelines to optimise patient outcomes. Design: Prospective cross-sectional survey was used to conduct a national audit. Setting: Community setting of CHF-MPs for patients after discharge. Sample: All CHF-MPs operating during 2005–2006 (n = 55). 10–50 consecutive patients from 48 programmes were also recruited (n = 1157). Main outcome measures: (1) Characteristics and interventions used within each CHF-MP and (2) characteristics of patients enrolled into these programmes. Results: Overall, there was a disproportionate distribution of CHF-MPs across Australia. Only 6.3% of hospitals nationally provided a CHF-MP. A total of 8000 post-discharge CHF patients (median, 126; IQR, 26–260) were managed via CHF-MPs representing only 20% of the potential national case load. Significantly, 16% of the case load comprised patients in functional New York Heart Association class I with no evidence of these patients having had previous echocardiography to confirm a diagnosis of CHF. Heterogeneity of CHF-MPs in applied models of care was evident with 70% of CHF-MPs offering a hybrid model (a combination of heart failure outpatient clinics and home visits), 20% conducting home visits and 16% an extended rehabilitation model of care. Less than half (44%) allowed heart failure nurses to titrate medications. The main medications that were titrated in these programmes were diuretics (n = 23, 96%), β-blockers (n = 17, 71%), ACE inhibitors (n = 14, 58%) and spironolactone (n = 9, 38%). Conclusion: CHF-MPs are being implemented rapidly throughout Australia. However, many of these programmes do not adhere to expert clinical guidelines for the management of patients with CHF. This poor translation of evidence into practice highlights the inconsistency and questions the quality of health-related outcomes for these patients.